Development of a Neuropsychological Intervention Package for Multiple Sclerosis (M.S) and Comparison of the Effectiveness of Neuropsychological Intervention and Acceptance and Commitment Therapy on Pain Catastrophizing in Patients with Multiple Scler - Shaygan Nik, Maryam; Rezaei Jamalooei, Hasan; NikYar, Hamidreza; Sobhani, Ahmad (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to examine the effectiveness of two therapeutic interventions based on a neuropsychological approach and Acceptance and Commitment Therapy (ACT) in reducing pain catastrophizing in MS patients. Methods and Materials: The research employed a mixed-methods (qualitative-quantitative) design, with the study population consisting of MS patients attending healthcare centers in Isfahan in 2023-2024. From this population, 45 individuals were randomly selected and assigned to three equal groups: experimental group 1 (15 participants), experimental group 2 (15 participants), and a control group (15 participants). The first group received treatment based on the neuropsychological approach, while the second group underwent ACT. Data collection tools included the Pain Catastrophizing Questionnaire and a demographic questionnaire, and data were analyzed using univariate analysis of covariance. Findings: The results indicated that both therapeutic interventions led to a significant reduction in pain catastrophizing in MS patients. The F-values for the magnification and rumination variables in the experimental groups were significantly higher than in the control group (p < 0.05). Conclusion: These findings suggest that both interventions can effectively reduce pain catastrophizing and may be considered effective treatment approaches.